The association of cuspAligned arcs with plasma in the magnetotail implies a closed magnetosphere - Milan,SE; Mooney,MK; Bower,GE; Taylor,MGGT; Paxton,LJ; Dandouras,I; Fazakerley,AN; Carr,CM; Anderson,BJ; Vines,SK (JGR: Space Physics, 2023)
We investigate a 15-day period in October 2011. Auroral observations by the Special Sensor Ultraviolet Spectrographic Imager instrument onboard the Defense Meteorological Satellite Program F16, F17, and F18 spacecraft indicate that the polar regions were covered by weak cusp-aligned arc (CAA) emissions whenever the interplanetary magnetic field (IMF) clock angle was small, |θ| < 45°, which amounted to 30% of the time. Simultaneous observations of ions and electrons in the tail by the Cluster C4 and Geotail spacecraft showed that during these intervals dense (≈1 cm−3) plasma was observed, even as far from the equatorial plane of the tail as |ZGSE| ≈ 13 RE. The ions had a pitch angle distribution peaking parallel and antiparallel to the magnetic field and the electrons had pitch angles that peaked perpendicular to the field. We interpret the counter-streaming ions and double loss-cone electrons as evidence that the plasma was trapped on closed field lines, and acted as a source for the CAA emission across the polar regions. This suggests that the magnetosphere was almost entirely closed during these periods. We further argue that the closure occurred as a consequence of dual-lobe reconnection. Our finding forces a significant re-evaluation of the magnetic topology of the magnetosphere during periods of northwards IMF.